Хищные клещи-фитосейиды (Parasitiformes, Phytoseiidae) Лесостепи УССР. Сообщение III. Определитель родов и видов - Колодочка, Л.А. (Вестник зоологии, 1974)
Morphology and histological structure of Hyphantria cunea Dr. gonads are studied. The processes of spermatogenesis are investigated at all the postembryonic stages of development. The process of sex cells formation and gonads growth are established to accelerate from the caterpillars of the IV age. Spermatogenesis in Hyphantria curea Dr. proceeds according to the type common to Lepidoptera. However in Hyphantria cunea Dr. at the pupa stage the paired gonads fuse into one, that is not observed in Bombyx mori L. and Antheraca pernyi G.-M.